Cultura organizacional en la Papelería y Tecnología T7 en el Cantón Montalvo - Galeas Pesantes, Ginger Margarita (2018)
The stationery market has a great boom since there is great demand that arise throughout the year, it is a product that is constantly rotating, as it is in the return to school, the day of independence, Valentine's Day between other special occasions, becoming a profitable business. The T7 Stationery and Technology is located in Montalvo Canton, province of Los Ríos, its commercial activity started in 2011 is currently 7 years in the Montalvino market, its parent is located on Avenida 25 de Abril in front of Colegio Jaime Roldos Aguilera , enjoys with two branches one in the center of the mentioned Canton in the avenue Antonio de la Bastida and Montalvo and the second dependence is located in the province of Bolívar in the Cantón Chillanes.